Serum retinol-binding protein 4 in stroke patients: correlation with T helper 17/regulatory T cell imbalance and 3-year cognitive function decline - Wang, Fei; Qin, Yaqin; Li, Zongyou (Frontiers in Neurology, 2023)
Objective Retinol-binding protein 4 (RBP4) promotes atherosclerotic progression and neuronal loss, whereas its association with cognitive impairment in stroke is unclear. Hence, this prospective study aimed to explore the association of serum RBP4 with the T helper (Th)17/regulatory T (Treg) cell ratio and its correlation with cognitive impairment in stroke patients. Methods Peripheral blood samples from 265 stroke patients and 50 healthy controls (HCs) were collected at enrollment for serum RBP4 (by enzyme-linked immunosorbent assay) and Th17 and Treg cells (by flow cytometry) determination. Additionally, stroke patients underwent routine follow-ups, and their Mini-Mental State Examination (MMSE) scores were assessed at baseline and in years 1, 2, and 3 after enrollment. Results Serum RBP4 was elevated in stroke patients compared to HCs (p < 0.001), with a good ability to differentiate stroke patients from HCs (area under the curve: 0.815). Serum RBP4 was positively associated with Th17 cells (p < 0.001) and the Th17/Treg cell ratio (p < 0.001) and negatively associated with Treg cells (p = 0.003) in stroke patients, whereas it was only positively associated with the Th17/Treg cell ratio (p = 0.027) but not with Th17 (p = 0.075) or Treg (p = 0.130) cells in HCs. Furthermore, increased serum RBP4 was associated with a lower MMSE score (p < 0.001) and a lower incidence of cognition impairment (p = 0.005) at enrollment in stroke patients, as were Th17 cells and the Th17/Treg cell ratio (all p < 0.050). The 1-, 2-, and 3-year MMSE scores in stroke patients were 25.9 ± 2.0, 25.3 ± 2.3, and 24.9 ± 2.3, respectively. More importantly, serum RBP4 was negatively correlated with 1-, 2-, and 3-year MMSE scores (all p < 0.001) and positively associated with 1-year (p = 0.013), 2-year (p = 0.007), and 3-year (p = 0.001) MMSE score declines in stroke patients. Conclusion Serum RBP4 is positively associated with a Th17/Treg cell imbalance and, more importantly, it is indicative of cognitive function decline within 3 years in stroke patients. Thus, early and timely interventions and physical rehabilitation are more necessary in stroke patients with high serum RBP4.